IMPORTANCE OF MANGROVE TO REDUCE THE TSUNAMI WAVE ENERGY - Purnamasari, Anastasia Neni Candra (Faculty of Agriculture, Janabadra University, 2017)
Mangrove has a very important role to reduce the tsunami wave energy. It is shown that the coastal areas have no vegetation or in this case will have an impact Mangrove forests greater damage due to tsunami waves than the coastal areas of vegetation. The purpose of the Term Paper is proved the importance of Mangrove to reduce the tsunami wave energy by comparing the various methods that have been observed in some case studies on the impact of the tsunami that occurred in several Asian countries in 2004 and case studies on ocean waves on the Gulf coast of south Florida. Based on the research results that could dampen Mangrove Tsunami wave energy. Tsunami wave energy can be reduced by several factors, namely mangrove species, tree size, vast mangrove forest, nature tree structure, and the size limit Mangrove forest (as far as how much of the ocean to the surface).